Comparison of Baseline Characteristics, Sociodemographics, and Gynecological Risk Factors Associated with Secondary Infertility of Females in Pakistan - Wafa Fatima; Abdul Majeed Akhtar; Asif Hanif; Aima Gilani; Syed Muhammad Yousaf Farooq (Mary Ann Liebert, 2024)
Introduction: Secondary infertility is characterized by the inability to conceive for a period of 1 year, after having previously conceived at least once. Objectives: To explore the risk factors of secondary infertility and compare sociodemographics and anthropometric variables of each studied group. Methods: Study was conducted at University Institute of Public Health, Faculty of Allied Health Sciences, The University of Lahore, collecting data from Gilani Ultrasound Center in 18 months after approval of synopsis. Total 690 females (345 cases and 345 controls) were enrolled. Participants were included in case group if they were 20?45 years of age, having any parity, and confirmed diagnosis of secondary infertility. Results: The mean age of cases and controls was 33.08???4.17 years and 31.37???4.36 years, respectively. The mean body mass index (BMI) in cases was 27.61???4.27?kg/m2, and in controls the mean BMI was 25.52???4.30?kg/m2. There was not a significant difference among religion that shows no association (p?=?0.73) with secondary infertility as profession has association with it (p?=?0.01). History of polycystic ovary syndrome, pelvic inflammatory disease, endometriosis, uterine fibroids, menorrhagia, intermenstrual bleeding, and history of abortion are associated with secondary infertility. Conclusions: While several sociodemographic features and medical disorders have been associated to secondary infertility, it is vital to stress that not all of these factors are controllable by medical therapy. Factors like age and certain medical issues may be unaffected by intervention. However, for controllable variables like BMI and certain medical diseases, focused therapies and lifestyle changes may reduce the chance of subsequent infertility.